MEDIA SIBER, APARAT, DAN PEMBERITAAN KEBERAGAMAN - Riris Loisa; Eko Harry Susanto; Ahmad Junaidi; Felicia Loekman (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
The up and down of relations between the government and the media have been the topic of various studies for decades. Historically, relations between the two parties were characterized by unequal power relations. Reform and development of digital communication technology gives hope for press freedom in producing and distributing information to the public free from government interference. This study aims to describe the relationship between cyber media and key informants, especially government officials in covering diversity issues. This research is based on research conducted with a normative theory perspective, applying a case study method for 2 (two) years, beginning with content analysis of 200 (two hundred) articles on diversity in cyber media, followed by discussions with 30 (thirty) media journalists cyber, 15 journalists in Jakarta, and 15 in Medan. In the second year, an electronic survey was conducted for cyber media journalists. The results of the study show that in reporting on the issue of diversity, cyber media actually makes government officials primary sources. This shows that the dynamics of cyber media relations and current government apparatus in terms of reporting on diversity issues are characterized by the closeness that was previously framed in power relations, currently in an urgent relationship of interest, accuracy, and risk management. The substance of this study provides input for journalists to be wiser in addressing technological advancements in various fields, especially cyber media.